Peran Pancasila Dalam Memupuk Persaudaraan Dan Toleransi Mahasiswa Di Kampus - Bunga Sundari Tamba; Divia Salwa Salsabillah; Elisabet Pasaribu; Salsabila Br Tohang; Ummu Hani (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
This research aims to describe facts in the field regarding the role, implementation, and factors that influence the application of Pancasila values for students. This research uses a qualitative approach with descriptive methods. Meanwhile, the data collection technique used in this research is a questionnaire. The results of this research show that the role of students in implementing Pancasila values is by having high tolerance, being active in social activities, having integrity as leaders based on Pancasila values, supporting the process of collective deliberation and decision making, and having a conscience. and put it into real action. Based on the results of a questionnaire conducted on Medan State University students regarding the implementation of one of the values contained in Pancasila, namely an attitude of tolerance towards cultural, ethnic and religious differences, the results showed that the majority of students had instilled and implemented it well. Meanwhile, the small number who do not understand and implement this attitude of tolerance may be caused by several internal and external aspects or factors.